Sex-dependent modulation of acute respiratory distress syndrome by Bacteroides acidifaciens: gut microbiome impact on lung inflammation - Staley, Shanieka; Walkup, Virginia; Oxendine, Stacey; Mauya, Zannatul; Williams, Jordan; Busbee, Philip Brandon; Wilson, Kiesha (Frontiers in Immunology, 2025)
Bacteroides acidifaciens (BA), a common gut commensal, is known to modulate immune responses, but its role in acute respiratory distress syndrome (ARDS) and potential sex-specific effects remain poorly understood. To investigate this, male and female mice were colonized with BA prior to induction of ARDS using dual doses of staphylococcal enterotoxin B (SEB), a potent superantigen that triggers cytokine storm–driven lung injury. Clinical parameters, histopathology, gene expression, ELISA, flow cytometry, and gut barrier assessments were used to evaluate outcomes. BA pre-treatment significantly improved lung function, and attenuated pulmonary inflammation in male mice, correlating with increased IL-22, expansion of γδ T cells, and upregulation of colonic tight junction proteins. In contrast, BA exacerbated ARDS symptoms in females, increasing Th17 responses, neutrophil infiltration, and IgA-associated immune activation while impairing gut barrier integrity. These findings reveal that BA exerts divergent, sex-dependent effects in ARDS, highlighting the critical need to consider sex as a biological variable in microbiome-based therapies targeting inflammatory lung disease.